Offshoreverksamheten i Arktis - En studie om hur offshoreverksamheten för oljeutvinning i Arktis kan komma att påverkas av oljepriset och klimatförändringen - Forslund, Johanna (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2013)
Due to decline in oil resources the price of oil has increased during resent years, resulting in a greater need and interest in finding new oil reserves. When interest in oil exploration in new areas increases, it also means that new potential markets for offshore operations will be created. The Arctic is a region where a quarter of the world's undiscovered oil and gas reserves are estimated to be located, which has increased the interest in oil exploration in the Arctic. Since the price of oil is considered to be a driving factor for the interest in oil exploration in the Arctic, this report examines how the price of oil might affect offshore operations in the Arctic. Since the ice in the Arctic is melting faster than scientists have predicted, it is also a relevant affecting factor to investigate. The purpose of this report is to examine how offshore operations in the Arctic might be affected by climate change and by the price of oil. The questions that form the basis of this report is how the price of oil affect offshore operations in the Arctic, and how the melting ice affect offshore operations in the Arctic. This report is formed by a qualitative method where data collection has been conducted through literature and an interview. Qualitative data obtained through the collection of data is presented in the report and is then analyzed. The results of this report show that the price of oil and the climate change affects the offshore activities in the Arctic. The Arctic could be a potentially important market for offshore operations, where exploration activities are expected to increase.